NUMERICAL COMPUTER SECTIONING OF STRESSED STATE OF THE SLUGS WITH CIRCULAR SECTION - A. N. Chichko; N. V. Andrianov; A. V. Demin (Литьë и металлургия, 2005)
The computer calculations of alternate distribution of temperatures and stresses in crystallizing round ingot with diameter 300 mm of low-carbon steel 20 are presented. There is determined the character of voltage excursion in secondary cooling zone along the length of ingot of circular section and in different cross-sections. The possibility of occurrence of asymmetry of longitudinal stresses in crosssection of ingot is theoretically shown.